Magnetic properties for the Mn2GeTe4 compound - Quintero, M. (2009)
Measurements of magnetic susceptibility χ, in the temperature range from 2 to 300 K, and of magnetization M vs. applied magnetic field B, up to 5 T, at various temperatures were made on polycrystalline samples of the Mn2GeTe4 compound. It was found that Mn2GeTe4 has a Néel temperature TN of about 135 K, shows mainly antiferromagnetic behavior with a very weak superimposed ferromagnetic component that is attributed to spin canting. Also, the magnetic results suggest that a possible spin-glass transition takes place at Tf≈45 K. The spin-glass order parameter q(T), determined from the susceptibility data, was found to be in agreement with the prediction of conventional spin-glass theory. The M vs. B results indicated that bound magnetic polarons (BMPs) occur in the compound, and that the effects from BMPs disappear at approximately 80 K. The M vs. B curves were well fitted by a Langevin type of equation, and the variation of the fitting parameters determined as a function of temperature. Using a simple spherical model, the radius of the BMP in the material was found to be about 27 Å; this value is similar to the effective Bohr radius for an acceptor in the II-IV-V2 and I-III-VI2 ternary semiconductor compounds. © 2008 Elsevier B.V. All rights reserved.